Studying Music During the Coronavirus Pandemic: Conditions of Studying and Health-Related Challenges - Rosset, Magdalena; Baumann, Eva; Altenmüller, Eckart (Frontiers in Psychology, 2021)
Objective: The coronavirus pandemic affects all areas of life. Performing arts and music studies have also experienced considerable changes, with university closures and a fluctuating return to normal and more limited operations. Prior studies detail the impact of the pandemic on college students, but we do not yet know what specific consequences it has for music students. The aim of this study is to examine the impact of the coronavirus pandemic on music students’ health, practicing behavior, and everyday life. Methods: In July 2020, we conducted an online survey of 80 students enrolled in performance and music education programs at a German music university and compared these data with data from a survey of 75 students at the same music university carried out in summer 2019. Results: The survey revealed that the coronavirus pandemic led to a decrease in practicing hours and an increase of stressful thoughts and feelings. Students were mostly satisfied with Corona-measures taken by the university. Of analyzed determinants, only general fear of health problems was identified as a significant predictor of mental health status. Mental health status did not significantly differ between students surveyed in 2019 and 2020. Conclusion: Knowledge about the specific challenges the pandemic poses for music students can help conservatories to better respond to the needs of their students. Specifically, this study will inform future measures supporting music students in coping with difficult situations like a pandemic.